Bacterial profile and prevalence of urinary tract infections in pregnant women in Latin America: a systematic review and meta-analysis - Henrique Diório de Souza; Giselle Rodrigues Mota Diório; Stela Verzinhasse Peres; Rossana Pulcineli Vieira Francisco; Marco Aurélio Knippel Galletta (BMC, 2023)
Abstract Background Given the physiological changes during pregnancy, pregnant women are likely to develop recurrent urinary tract infections (UTIs) and pyelonephritis, which may result in adverse obstetric outcomes, including prematurity and low birth weight preeclampsia. However, data on UTI prevalence and bacterial profile in Latin American pregnant women remain scarce, necessitating the present systematic review to address this issue. Methods To identify eligible observational studies published up to September 2022, keywords were systematically searched in Medline/PubMed, Cochrane Library, Embase, Web of Science, and Bireme/Lilacs electronic databases and Google Scholar. The systematic review with meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and the quality of studies was classified according to the Strengthening the Reporting of Observational Studies in Epidemiology guidelines. The meta-analysis employed a random-effects method with double-arcsine transformation in the R software. Results Database and manual searches identified 253,550 citations published until September 2022. Among the identified citations, 67 met the inclusion criteria and were included in the systematic review, corresponding to a sample of 111,249 pregnant women from nine Latin American countries. Among Latin American pregnant women, the prevalence rates of asymptomatic bacteriuria, lower UTI, and pyelonephritis were estimated at 18.45% (95% confidence interval [CI]: 15.45-21.53), 7.54% (95% CI: 4.76-10.87), and 2.34% (95% CI: 0.68-4.85), respectively. Some regional differences were also detected. Among the included studies, Escherichia coli (70%) was identified as the most frequently isolated bacterial species, followed by Klebsiella sp. (6.8%). Conclusion Pregnant women in Latin America exhibit a higher prevalence of bacteriuria, UTI, and pyelonephritis than pregnant women globally. This scenario reinforces the importance of universal screening with urine culture during early prenatal care to ensure improved outcomes. Future investigations should assess the microbial susceptibility profiles of uropathogens isolated from pregnant women in Latin America. Trial registration This research was registered at PROSPERO (No. CRD42020212601).